The Effects Of Acute Kidney Injury On The Outcomes Of Patients With Gastrointestinal Bleeding - Mahmud, Mahvesh; Baqai, Khurram; Kumar, Ashok (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the clinical outcomes of patients with acute kidney injury in patients with upper gastrointestinal bleeding (UGIB), as it is a very frequently encountered condition with high morbidity and treatment costs. We aimed to study the differences in clinical outcomes in patients with UGIB who developed acute kidney injury (AKI) and those who did not. Methods: This cross-sectional study was conducted between Jan 1 and Jun 30, 2023, at a private hospital in Karachi. 200 cases with upper gastrointestinal bleeding were recruited by non-probability sampling after participant assent. 100 patients comprised the acute kidney injury (AKI group) and 100 patients were without AKI. Participants documented age, gender, and co-morbidities in a self-structured questionnaire. Clinical outcomes i.e. hypoalbuminemia, hospital stay and mortality were evaluated and compared. Results: Mean age was 45.03+9.17 years in AKI group and 45.57+9.31 years in without AKI, p-value=0.680, albumin levels in AKI was 2.74+0.43 and without AKI 3.18+0.31, p-value=0.00, Hb level in AKI group was 9.07+0.83 and without AKI 9.54+1.04, p-value=0.001, mean hospital stay in AKI group was 5.21+1.00 and without AKI group 4.20+0.96 days, p-value=0.000. A comparison of the two groups regarding gender and clinical outcome shows that 58 (58%) in AKI and 56%(56) without AKI were male whereas 42 (42%) in AKI and 44 (44%) without AKI were females, mortality in AKI group was 27(27%) and in without AKI group 8(8%) cases, p-value=0.000. Conclusion: We concluded that the rate of clinical outcome in terms of hospital stay, hypoalbuminemia and mortality was adverse in upper gastrointestinal bleeding with AKI than those without AKI. Keywords: Acute kidney injury, gastrointestinal bleeding, clinical outcome.